Analisa Keefektifan Jaringan Local Area Network (intranet) Universitas Muria Kudus - Nurkamid, Mukhamad (Universitas Muria Kudus, 2011)
Local networks, or often known by the term intranet is how to connect a series of computer organization (institution) is limited to a certain scope. Local Area network often known as the intranet is also referred to as the use of internet network for locally.In this study the authors tried to reveal a little more technology developed to build an intranet network at the University of Muria Kudus associated with the management and utilization is managed by the Technical Implementation Unit Planning Information System (UPT PSI) through the experimental test some components of builders like Mikrotik, Cisco Router, Switch Manageable, Distribution Switch , Proxy Server and DNS Server.